1999
DOI: 10.1115/1.2841330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Upstream Rotor Vortical Disturbances on the Time-Averaged Performance of Axial Compressor Stators: Part 1—Framework of Technical Approach and Wake–Stator Blade Interactions

Abstract: In a two-part paper, key computed results from a set of first-of-a-kind numerical simulations on the unsteady interaction of axial compressor stators with upstream rotor wakes and tip leakage vortices are employed to elucidate their impact on the time-averaged performance of the stator. Detailed interrogation of the computed flow field showed that for both wakes and tip leakage vortices, the impact of these mechanisms can be described on the same physical basis. Specifically, there are two generic mechanisms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…An alternative opportunity to assess the comparison method was to run a twodimensional case with boundary layers on the blade surfaces and quantify the effect of upstream wake velocity defect on boundary layer loss. Such a study by Valkov [24] showed that the loss increases linearly with upstream wake velocity defect. Computations were carried-out for three different wake sizes and the results are in accord with Valkov's findings (Figure 2.5), which were based on using a high order numerical scheme, namely, the spectral element method.…”
Section: Methods Assessment and Validationmentioning
confidence: 96%
“…An alternative opportunity to assess the comparison method was to run a twodimensional case with boundary layers on the blade surfaces and quantify the effect of upstream wake velocity defect on boundary layer loss. Such a study by Valkov [24] showed that the loss increases linearly with upstream wake velocity defect. Computations were carried-out for three different wake sizes and the results are in accord with Valkov's findings (Figure 2.5), which were based on using a high order numerical scheme, namely, the spectral element method.…”
Section: Methods Assessment and Validationmentioning
confidence: 96%
“…It seems that the mixing-plane assumption at the interfaces between the rotating and stationary domains causes this discrepancy. The beneficial effects of blade row interaction on rotor performance were studied by Valkov and Tan [12], Sirakov and Tan [13], and Graf et al [14]. Valkov and Tan [12] showed that the upstream wake recovery increased the pressure rise in the downstream passage by 1 to 3%.…”
Section: Calculation Models and Methodsmentioning
confidence: 99%
“…The beneficial effects of blade row interaction on rotor performance were studied by Valkov and Tan [12], Sirakov and Tan [13], and Graf et al [14]. Valkov and Tan [12] showed that the upstream wake recovery increased the pressure rise in the downstream passage by 1 to 3%. Sirakov and Tan [13] explained that the upstream wake suppressed double leakage of the tip clearance flow, thereby enhancing the pressure rise by about 2%.…”
Section: Calculation Models and Methodsmentioning
confidence: 99%
“…Relevant discussions were made in detail by Adamczyk (1996). Deregel and Tan (1996) and Valkov and Tan (1998) for compressor stages, referring to 'wake recovery model of Smith (1966). Even though such a wake recovery existed in the present cascade, it seemed quite difficult to distinguish it from the viscous effect.…”
Section: Measurements Of the Wake -Affected Cascade Lossmentioning
confidence: 96%